Implementation Of Logo Copyright Protection Based On Copyright Law In Yogyakarta - Wardhana, Ardiyanto (Fakultas Hukum Dehasen, 2025)
This article aims to explain the legal protection of copyright for unregistered logos and identify the causes of copyright infringement. Additionally, it discusses the factors influencing creators' decisions on whether to register their logo copyrights. This study employs both literature research and field research methods. Literature research is conducted to obtain theoretical data, while field research aims to collect primary data through interviews with respondents and informants relevant to the issues being studied. The findings indicate that copyright protection for logos in Yogyakarta has not been fully effective, as evidenced by ongoing copyright infringements on unregistered logos. Despite the declarative principle stating that copyright belongs to the first party to publish it, violations still occur. Several factors contribute to these infringements, including a lack of legal awareness regarding copyright, the desire for quick financial gain, technological advancements, and difficulties in enforcement. To safeguard logo copyrights, registration can serve as initial proof of ownership. However, many creators do not register their logos due to the large number of designs they produce and limited knowledge of copyright law. Therefore, the Yogyakarta Regional Office of the Ministry of Law and Human Rights is expected to enhance copyright protection for logos by raising public awareness about the importance of safeguarding intellectual property. Additionally, copyright holders whose rights have been violated are encouraged to pursue legal action, either through litigation or non-litigation, to ensure their logo rights are not arbitrarily taken.